PENGARUH KOMITE AUDIT DAN AUDIT EKSTERNAL TERHADAP KINERJA PERUSAHAAN (Studi Empiris pada Perusahaan Finansial dan non-Finansial dalam Indeks LQ45 Tahun 2019-2021) - Munir, Ghadiazka Azzata; Cahyonowati, Nur (Diponegoro Journal of Accounting, 2024)
The objective of this study is to investigate the influence of committee audit characteristics and external audit quality on firm performance. The variables used in this study are committee audit (size & frequency of meeting) and external audit quality (BIG4 & auditor independence) as the independent variable, while firm performance (Tobin’s Q) used as the dependent variable.The study uses a sample of 2019-2021 LQ45 companies that listed on the Indonesian Stock Exchange and Bloomberg Terminal with a total of 81 samples using purposive sampling with conditions that have already been determined. The analytical method utilized in this study is the multiple regression HCSE analysis.The result of this study showed that audit committee size & frequency of meeting and auditor independence has no influence over firm performance. While BIG4 has positive influence over firm performance.